Analisis Hubungan Kebisingan Pasar Mangu, Jalan Raya Manguraya, Dan Bandara Adi Soemarmo Dengan Konsentrasi Belajar Siswa Di SMP Negeri 1 Ngemplak - Ratna Widyaningtyas; Wahyu Kisworo; Satria Aji Pambudi; Muchammad Sholiqin; Siti Rachmawati (Prosiding Sains dan Teknologi, 2022)
Noise is a type of environmental pollution in the form of sound that comes from a human activity. The impact of noise is disturbing comfort in the environment. The purpose of this study was to determine the level of influence of the noise relationship from the activities of the Mangu Market, Jalan Raya Manguraya, and Adi Soemarmo Airport on the concentration of students' learning at SMPN 1 Ngemplak. The research method is observational with a cross sectional analysis approach. Noise research was conducted at 09.00-10.00; 10.00-11.00; and 11.00-12.00 with 2 sampling points, namely roads and classrooms which respectively obtained an average result of 68.97dB and 55.73dB. Based on the data that has been obtained, the noise at SMPN 1 Ngemplak exceeds the threshold set by KepMen LH No. 48/MNLH/11/1996, which is 55 dB for the school area. Data analysis was carried out with the Chi-Square test, obtained a probability value of 0.001<0.05. So it is stated that there is a significant relationship between the impact of noise that occurs at SMPN 1 Ngemplak with the concentration of student learning. Recommendations for reducing noise that can be done include planting trees around schools, building fences with vines, changing the function of classes near the highway into warehouses or teachers' offices that have minimal learning processes, reducing the percentage of windows and increasing the use of curtains, and changing building period. Keywords: Airport Activity, Highway Activity, Market Activity, Noise, School